1985
DOI: 10.1104/pp.79.2.411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature, Oxygen, and Gibberellic Acid on the Development of Photosensitivity in Oldenlandia corymbosa L. Seeds during Their Incubation in Darkness

Abstract: Two successive phases can be distinguished in the development of the responsiveness to light in Oldenlandia corymbosa L. seeds during their incubation in darkness. During phase I, the responsiveness to light increases with time if there is sufficient 02, and the higher the temperature, the faster the increase. This phase is stimulated by gibberellic acid. During the following phase (II), seeds remain responsive to light at 10 or 20°C, but lose their responsiveness at higher temperature (-30°C). This second pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…4). Such oxygen-dependent response to light, which was previously reported in negative photoblastic Bromus rubens and Amaranthus caudatus Gutterman et al 1992) and positive photoblastic Oldenlandia corymbosa (Corbineau & Côme 1985) probably explains the role played by the covering structures in the sensitivity of barley grains to light. Using micro-sensor, Hoang et al (2013a) recently demonstrate that O2 tension in the embryo under the seed-covering structures was 15.8% at 15°C, and considering that O2 solubility is higher at 10°C than at 15°C, the inhibitory action of blue light cannot only be explained by the reduced oxygen supply, as isolated embryos easily germinate in blue light in 15% O2 at 10°C (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…4). Such oxygen-dependent response to light, which was previously reported in negative photoblastic Bromus rubens and Amaranthus caudatus Gutterman et al 1992) and positive photoblastic Oldenlandia corymbosa (Corbineau & Côme 1985) probably explains the role played by the covering structures in the sensitivity of barley grains to light. Using micro-sensor, Hoang et al (2013a) recently demonstrate that O2 tension in the embryo under the seed-covering structures was 15.8% at 15°C, and considering that O2 solubility is higher at 10°C than at 15°C, the inhibitory action of blue light cannot only be explained by the reduced oxygen supply, as isolated embryos easily germinate in blue light in 15% O2 at 10°C (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…; Gutterman et al . ) and positive photoblastic Oldenlandia corymbosa (Corbineau & Côme ) probably explains the role played by the covering structures in the sensitivity of barley grains to light. Using micro‐sensor, Hoang et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that low water availability during droughts can affect the perception of light signals by seeds and the recruitment pattern of seedlings once soils return to field capacity (Botto et al ). In contrast, the effects of water excess on light perception and signalling of the environmental cues breaking seed dormancy have not been addressed, even though hypoxia is known to change seed responsiveness to light in upland plants (Corbineau & Côme ; Hoang et al ). Given that correct perception of signals that break dormancy may be essential to avoid underwater germination, the null hypothesis would be that E. crus‐galli seeds are equally able to perceive light and temperature regimes under hypoxic floodwater as under normoxic conditions, typical of drained soils.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the sensitivity of seeds to O 2 deprivation decreases with decreasing temperature, because of reduced respiratory activity and the higher solubility of O 2 in water (Côme and Tissaoui, 1973; Corbineau and Côme, 1995). The acquisition of responsiveness to light of Oldenlandia corymbosa seeds during imbibition requires at least 3.5% O 2 (Corbineau and Côme, 1985), while continuous white light reinforces the sensitivity to O 2 deprivation of negatively photosensitive seeds (Corbineau et al , 1992; Gutterman et al , 1992).…”
Section: Introductionmentioning
confidence: 99%